The High Efficiency fast-Response GAmma (HERGA) detector based on SiPM readout - Altomare C.; Cerasole D.; Di Venere L.; Fanchini E.; Gargano F.; Giordano F.; Loparco F.; Loporchio S.; Mastroserio A.; Morichi M.; Pantaleo F.R.; Serini D.; et al. (EPJ Web of Conferences, 2023)
Gamma-ray spectroscopy and gamma-ray imaging are two complementary techniques used for the localization and the identification of radioactive sources containing gamma-ray emitting radioisotopes. The radioactivity monitoring is focused on the detection of both artificial and environmental radioactive sources like Naturally Occurring Radioactive Materials (NORM). This kind of contamination becomes dangerous when the detection of the unwanted substances exhibits a concentration significantly above the environmental radioactive background radiation levels. For this purpose, we have developed, tested and shown a High Efficiency fast-Response GAmma (HERGA) detector useful for the identification of radionuclides and for gamma-ray imaging. A first version of the gamma detector prototype was composed of 16 CsI(Tl) scintillating crystals of 3x3x10 cm3 size, arranged in 4x4 matrix coupled with standard Photomultiplier tubes (PMTs). An image reconstruction of a radioactive gamma emitter source is possible using the coded mask technique, in which a 7x7 mask, made of Plastic and Tungsten tiles, is placed in front of the detector and a pattern recognition algorithm based on classical statistical methods (Kolmogorov Smirnov) is used to reconstruct the source position. The measurements carried out showed a point spread function (PSF) of a few mrad for pointlike sources. The Minimum Detectable Activity (MDA) was also determined in the case of pointlike radioactive sources. In this contribution we will present an update of the HERGA detector prototype in which Silicon Photomultipliers (SiPMs) are used in place of the PMTs. SiPMs provide similar or even better performance compared to the standard PMT sand provide benefits in terms of lower power consumption and reduced cost and compactness. The advantages of the SiPM technology are also characterized by the robustness of the photosensor that makes the new prototype compact, portable, ideal for in-situ and real-time. We will show a comparison between the results obtained with the newest SiPM read-out technology with respect to those obtained with the PMT one, in terms of energy and spatial resolution. The imaging performance is also in phase of testing in order to localize extended radioactive sources such as for example NORM samples or to detect inaccessible or hidden nuclear waste.